New localities of Myrmecophaga tridactyla (Linnaeus, 1758), Giant Anteater (Myrmecophagidae), in the southern region of Minas Gerais state, Brazil - Lasmar, Dunia; de Moura, Aloysio Souza; Machado, Felipe Santana; Zanzini, Antônio Carlos da Silva; de Melo, Lucas Amaral; Fontes, Marco Aurélio Leite (Boletim do Museu Paraense Emílio Goeldi - Ciências Naturais, 2025)
Myrmecophaga tridactyla (Linnaeus, 1758), species commonly known as the giant anteater, has had its geographic distribution reduced due to several factors (natural and anthropogenic environmental changes, low reproductive rate, resource depletion, conflicts and hunting). The species is currently classified as ‘Vulnerable’ at local, national and global levels. This study reports two new records of M. tridactyla in southern Minas Gerais, Brazil, in the municipalities of Lavras and Santo Antônio do Amparo, with a six-month interval between sightings. These records, obtained through direct observation and camera traps, identify new occurrence locations for the species and reinforce the need for further studies and targeted conservation initiatives.
Keywords: Endangered species; Mammal; Xenarthra; Geographic distribution